Drug Use Evaluation of Antimicrobials in Healthcare Resource Limited Settings of India - Rathinavelu, Mohanraj; Satyagama, Suvarchala; Reddy, Ramkesava; Padmanabha Reddy, Yiragamreddy (Indian Journal of Pharmacy Practice)
Background: Antimicrobial medications are considered as the greatest discovery of the twentieth century. The emergence of antibiotic resistant bacteria is a major problem throughout the world and a rational use of antibiotics is therefore very important. Drug utilization research facilitates the rational use of drugs and suggests a way to improve prescribing habits. Aim: The study was designed to evaluate the pattern of drug utilization in inpatients of general medicine department of a secondary care referral hospital of India. Methods: The data was obtained prospectively from 80 inpatients prescriptions, the DDD/100 bed days was calculated were multiple antimicrobial drug use is very common. Results: The study showed inappropriate drug use in case of dengue fever with ceftriaxone and ciprofloxacin, upon observations drugs like ceftriaxone, augmentin and primaquine were found to be used in a higher proportions. On calculation of DDD the drug nitrofurantoin use was high when compared to WHO DDD. Also, anti-malarial drug primaquine use was higher. Conclusion: In conclusion, the study indicate that there is a substantial scope for improvement in prescribing pattern by adhering to standard guidelines of treatment and restriction policies to promote rationality drug use.
Keywords: Anatomical and therapeutic classification system; Antibiotic restriction policies; Defined daily dose; Drug utilization research; Pharmaceutical care; Rational use